Золушка: выжыкыл : пиналъёслы / Шарль Перро - Перро Шарль (Удмуртской книжной издательство, 1954)
Экземпляры: КР (20020330) / Инвентарный номер: у7214 / Сис.шифр: И(Фр) / Авт.знак: П 27 / ГРНТИ: 17.82 / ББК: 84(4/8)